Komparasi Disposisi Matematis pada Siswa Berkepribadian Melankolis dan Sanguinis - Saryati Saryati; Budiyono Budiyono; Riawan Yudi Purwoko; Teguh Wibowo (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2020)
The purpose of this study was to determine the mathematical disposition of students who have sanguine and melancholic personality types, and whether the mathematical disposition of students with sanguine types is higher than melancholic types. The population in this study was 260 seventh grade students of Junior High School in the Pituruh district. Sampling using a proportionate random sampling technique was taken as many as 65 students. Data collection was carried out using questionnaires and tests. The results of the first study showed that the mathematical disposition of seventh-grade students in the Pituruh Subdistrict in the 2019 school year in terms of the sanguine and melancholic personality types of more than 60%. The second research result shows that there are differences in mathematical disposition between sanguine and melancholic types, where the mathematical disposition of students with sanguine personality types is higher than students with melancholic personality types.